EFFICIENCY OF REGIONAL FINANCIAL MANAGEMENT OF BEKASI REGENCY IN 2016-2020 - Susanti Hartono, Rina (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2024)
The implementation of regional autonomy is a form of implementation of the principle of decentralization so that the implementation of regional government affairs runs orderly. In the context of achieving an orderly government, the regional government and the legislative body implement regional government administration. The reforms also impacted financial management in the government sector, so at that time regional financial accounting received great attention from various parties. This study aims to determine the efficiency level of regional financial management in the Bekasi Regency from 2016 to 2020. The study was carried out in the Bekasi Regency Government, West Java Province. Based on the existing problems, this type of research is descriptive qualitative that is, by doing calculations on the financial data obtained to solve existing problems following the research objectives. The data collection technique used is to use observation, documentation, and literature study. The results of the study show that from 2016 to 2020, Bekasi Regency's regional finances were at a less efficient level with an average percentage of 98.8%.